Pollution load management to improve water quality of Sungai Pusu - Zainudin, Zaki; Mohd Said, Noorwahidah Syaira; Jami, Mohammed Saedi; Salleh, Md. Noor (AENSI Publications, 2014)

(untitled)
Sg. Pusu is a river that flows through the campus of the International Islamic University Malaysia (IIUM). The river is murky in appearance, particularly after a rainfall event, which reflects elevated suspended solids (SS) levels. This study aims to characterize the water quality conditions of the river under high flow conditions, particularly in relation to SS, via a QUAL2K modeling approach and to determine the amount of load reduction needed to a achieve a Class II denotation of the National Water Quality Standards (NWQS). A total of 30 water quality stations were identified on the main-stem and east tributary for grab sample collection. The analysis results showed the SS levels ranged between 10 – 1,790 mg/L on the main-stem, whereas the levels were generally higher in the tributary, ranging between 10 – 140 mg/L. The increase was most significant in the middle segment of the river, where the levels went beyond 500 mg/L. The modeling revealed that at least 2,880 kg/hr of SS had to be reduced to achieve the Class II target. Sand-mining and developmental activities upstream were the primary source of SS. Besides this; BOD5 and NH3-N levels were also elevated, beyond the Class IV denotation. To achieve Class II, at least 122 kg/hr of BOD5 and 42 kg/hr of NH3-N have to be reduced.